Sustainable management of agriculture products value chain in responses to climate change for South-Eastern coast of Bangladesh - Prabal Barua; Syed Hafizur Rahman; Maitri Barua (Modern Supply Chain Research and Applications, 2021)
Purpose: This paper is designed to assess the sustainable value chain approaches for marketing channel development opportunities for agricultural products in coastal Bangladesh to combat climate change through an approach of community-based adaptation options. Design/methodology/approach: The study was designed to select the potential value chain candidate and to analyze and establish a value chain map to benefit the crop farmers. In this connection, the resources of the whole context were evaluated. The approach uses few tools to generate three outputs, the last of which are the final list of value chains selected for in-depth assessment to design interventions as community-based adaptation practices of the study to combat climate change in the study areas. Findings: The study demonstrated that the difference in the institutional circumstances of the end markets of the agriculture products is connected to the different categories of harmonization and control of the facilitating environment throughout the supply chains. National and local networks improve the value chain in terms of the value addition of the agriculture products, technology improvement, market access and profitability of the products. Strengthening the weak financial structure, focus more on formal financial systems and resolving sociocultural and climate change-induced hazard concerns are the major concerns on the development of value chains in the countries. Apparently, guarantee for good governance, checking illegal and unregulated market contexts, proper mitigation measures to climate change are some paramount important issues for the sustainable management of livelihood, yield, income and development. Practical implications: All kinds of stakeholders of the agriculture product value chain should focus on competitiveness and productivity and look for and exploit multiple ways to add value once initial success has been attained with a single deal. Ensuring sustainability within the value chains is an important feature to cater to the challenges and changing demands of the age. Originality/value: The study will help to established a sustainable value chain approach in response to climate change, which process will help to existent opportunities for firms to manage the issue of climate risk by codeveloping and employing adaptation options that may be more preferred or accepted by consumers across the entire chain for the sustainable management of livelihood, yield, income and development.
Keywords: 650; Sustainability; Climate change; Adaptation; Value chain; Agriculture crops